Multiple origins, uncertain destinies : Hispanics and the American future - Tienda, Marta; Mitchell, Faith, 1952- (Online access: NCBI NCBI Bookshelf., 2006)
Given current demographic trends, nearly one in five U.S. residents will be of Hispanic origin by 2025. This major demographic shift and its implications for both the United States and the growing Hispanic population make Multiple Origins, Uncertain Destinies a most timely book. This report from the National Research Council describes how Hispanics are transforming the country as they disperse geographically. It considers their roles in schools, in the labor market, in the health care system, and in U.S. politics. The book looks carefully at the diverse populations encompassed by the term Hispanic, representing immigrants and their children and grandchildren from nearly two dozen Spanish-speaking countries. It describes the trajectory of the younger generations and established residents, and it projects long-term trends in population aging, social disparities, and social mobility that have shaped and will shape the Hispanic experience.